2007
DOI: 10.1111/j.1365-2907.2007.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sarcoptic mangeSarcoptes scabieion the British foxVulpes vulpespopulation

Abstract: 1. Disease epizootics can significantly influence host population dynamics and the structure and functioning of ecological communities. Sarcoptic mange Sarcoptes scabiei has dramatically reduced red fox populations Vulpes vulpes in several countries, including Britain, although impacts on demographic processes are poorly understood. We review the literature on the impact of mange on red fox populations, assess its current distribution in Britain through a questionnaire survey and present new data on resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(32 citation statements)
references
References 127 publications
(115 reference statements)
0
29
0
3
Order By: Relevance
“…sity conservation, depending on the management scheme used. In some areas of the world, the implementation of agro-ecosystems have increased habitat spatial heterogeneity with the maintenance of both agriculture and native patches in the landscape, which have been beneficial for many mammals, including mice and bats (Macdonald et al, 2007). This positive effect is often associated with habitat complementation processes in which different patches contain different resources necessary to the population survival (Dunning et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…sity conservation, depending on the management scheme used. In some areas of the world, the implementation of agro-ecosystems have increased habitat spatial heterogeneity with the maintenance of both agriculture and native patches in the landscape, which have been beneficial for many mammals, including mice and bats (Macdonald et al, 2007). This positive effect is often associated with habitat complementation processes in which different patches contain different resources necessary to the population survival (Dunning et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on plants, insects, birds and mammals have shown that organic farming practices can counteract the negative effects of agriculture intensification (Beecher et al, 2002;Fischer et al, 2011;Holzschuh et al, 2006;Macdonald et al, 2007;Roschewitz et al, 2005). However, the magnitude of their effects seems to vary greatly, particularly among taxa and across landscapes (BatĂĄry et al, 2011;Bengtsson et al, 2005;Winqvist et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Kleijn and Sutherland 2003;Knop et al 2006;Whitthingham 2007). Until very recently, their role in enhancing biomass along food chains has not been a major focus of research (Shore et al 2005;Aschwanden et al 2007;Askew et al 2007;MacDonald et al 2007;Reid et al 2007). This is surprising because ecosystem functionalities largely depend upon major fluxes of biomass and energy from the lower to the upper trophic levels; a few dominant producer and consumer species usually constitute the basic architecture of an ecological community.…”
Section: Introductionmentioning
confidence: 96%